Police acts (central and states) - "Sethi's, R. B." (Allahabad, 1997)
Police Acts, Central and States, provide a new field for study and research with a view to assess the progress in accomplishment of police purpose in protecting the health, safety and morals of the community
Keywords: Bare acts